Determining the Relationships between Factors Affecting Adolescents’ Happiness in OECD Countries - Young-Chool Choi; Ji-Hye Lee; Ji-Hyun Jang (New Innovations in Economics, Business and Management Vol. 4, 2022)
The goal of this research is to look into the causal linkages between major educational parameters and teenage happiness, as well as to make policy recommendations for how 20 OECD countries might improve their levels of adolescent happiness. The HBSC score of adolescents from 20 OECD countries was selected as an indicator for happiness, and a number of independent variables such as per capita GDP and per capita educational expenditure were included in the analysis. A structural equation model was employed for the analysis. Per capita educational expenditure, educational decentralisation level, number of pupils per teacher, and other variables were found to have a direct impact on happiness in the study. The greatest influence was exerted by per capita educational expenditure. Of the paths to adolescent happiness, those that contained a significant indirect effect were “per capita GDP \(\) per capita educational expenditure \(\) happiness” and “educational decentralization \(\) number of students per teacher \(\) happiness”, which were significant at the level of p < 0.05. Compiling the paths toward adolescent happiness focusing on the significance of these direct and indirect effects shows that the “per capita GDP \(\) per capita educational expenditure \(\) happiness” path has the greatest effect.